LIMITATION OF CONCLUSION TECHNOLOGY TRANSFER TREATIES - Загрішева, Надія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: to analyze and study the legislation of Ukraine and a number of other countries regarding the availability and types of restrictions when concluding commercial agreements in the field of technology transfer. The novelty of this work is that for the first time the economic and legal affiliation of the technology transfer sphere is investigated. Research methods: an analysis of foreign experience in categories of entrepreneur and merchant is determined. Classification of international acts in the field of business entities. Results: a legal analysis of the legislation of Ukraine, Japan, the USA, some countries of Latin America concerning the restrictions on the conclusion of contracts and the existence of restrictive conditions has been carried out. Discussion: problems of concluding an economic contract for technology transfer in the presence of restrictions.